Optimizing lifetime reproductive output: intermittent breeding as a tactic for females in a long-lived, multiparous mammal - Deprez, M; Giminez, O; McMahon, CR; Mark Hindell; Harcourt, RG (2018)
In iteroparous species, intermittent breeding is an important life‐history tactic that can greatly affect animal population growth and viability. Despite its importance, few studies have quantified the consequences of breeding pauses on lifetime reproductive output, principally because calculating lifetime reproductive output requires knowledge of each individual's entire reproductive history. This information is extremely difficult to obtain in wild populations. We applied novel statistical approaches that account for uncertainty in state assessment and individual heterogeneity to an 18‐year capture–recapture dataset of 6,631 female southern elephant seals from Macquarie Island. We estimated survival and breeding probabilities, and investigated the consequences of intermittent breeding on lifetime reproductive output. We found consistent differences in females’ demographic performance between two heterogeneity classes. In particular, breeding imbued a high cost on survival in the females from the heterogeneity class 2, assumed to be females of lower quality. Individual quality also appeared to play a major role in a female's decision to skip reproduction with females of poorer quality more likely to skip breeding events than females of higher quality. Skipping some breeding events allowed females from both heterogeneity classes to increase lifetime reproductive output over females that bred annually. However, females of lower quality produced less offspring over their lifetime. Intermittent breeding seems to be used by female southern elephant seals as a tactic to offset reproductive costs on survival and enhance lifetime reproductive output but remains unavoidable and driven by individual‐specific constraints in some other females.